The "Cooperative School of Maringá" or a school with "public and free education with private micromanagement" (1991-1992): A charter school experience in Brazil avant la lettre - Mario Luiz Neves de Azevedo (Arizona State University, 2018)
The article analyzes the experience of privatization of municipal public schools in Maringá (Paraná - Brazil) between 1991 and 1992, called "Cooperative School of Maringá", considered by the municipal administration (1989-1992) as a school of "public and free education with private micromanagement". The article also presents the concept of New Public Management (NPM) and demonstrates similarities between the model of privatization in Maringá and charter schools in the USA.